Spatial economic aspects of the environment and environmental policy: New directions for research - Shelby Gerking (European Regional Science Association (ERSA), 1998)
This paper outlines major new research directions for research on spatial or interregional effects of the environment and envrionmental policy. It attempts to define and characterize key research questions that lie at the intersection of environmental and resource economics and regional and urban economics. This intersection is of considerable importance because at least some factors of production are mobile, both domestically and worldwide. In consequence, information concerning the value of environmental attributes is revealed when people and firms relocate. Additionally, environmental policy changes can alter the interregional or international distributions of factor incomes, population, and production of goods and services.
Keywords: 330